The Role of Educational Philosophy in Shaping Curriculum and Pedagogy - Pradip Kumar Singha (Journal of Innovation in Education and Social Research, 2025)
Educational philosophy plays an important role in shaping curriculum and teaching practices. It provides the basic ideas that inform how we teach and learn. This study looks at how different philosophical traditions affect curriculum design, instructional methods, and the overall goals of education. It examines Western philosophies such as idealism, realism, pragmatism, and critical theory, while also noting the drawbacks of leaving out non-Western viewpoints. The focus is on teenagers and school-level education, especially regarding AI tools used in education. By looking at metacognition and self-regulated learning (SRL), the research shows how different philosophical views influence the use of technology in classrooms. The findings indicate that philosophy not only sets the goals of education but also shapes how knowledge is shared and developed. In the end, the study highlights the importance of philosophical exploration in keeping curriculum and teaching practices relevant and transformative for society.